Do homeroom teachers affect students' academic achievement in China's middle schools?. Issue 4 (23rd February 2021) - Wang, Tianheng; Yang, Dan
ABSTRACT: While the effect of teacher quality on students' achievement is widely documented in the literature, relatively little is known about the impact of teachers' non-instructional role. By exploiting the random assignment of students and homeroom teachers to classrooms within the same grade and school, the paper finds that students' test scores for a subject can be improved if the subject is taught by a homeroom teacher. The mechanism analysis suggests that the impact could be driven by the better interaction between homeroom teachers and students.